X-RAY DIFFRACTION AND MÖSSBAUER SPECTROSCOPY INVESTIGATIONS OF THE (Al, Ni, Co)-DOPED AgFeO2 SYNTHESIZED BY HYDROTHERMAL METHOD - Siedliska, Karolina (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2020)
Delafossite AgFeO2, AgFe0.9Al0.1O2, AgFe0.9Ni0.1O2, and AgFe0.9Co0.1O2 powders were synthesized by hydrothermal method. The structural analysis and hyperfine interactions investigations were performed by X-ray diffraction and the Mössbauer spectroscopy. It was found that the (Al, Ni, Co)-doped delafossite phases with traces of metallic silver can be obtained during hydrothermal synthesis. Investigations revealed that the type of the incorporated element has an impact on the structural properties of the obtained delafossites. However, doping of cobalt, nickel, and alumina ions to the AgFeO2 delafossite structure does not cause significant changes in the values of the hyperfine interactions parameters. The of the Mössbauer spectra confirm the paramagnetic character of the obtained compounds at room temperature.